Desarrollo de branding para la marca de medias Söco: diseño de manual de identidad - Rojas Ortiz, Natalia Carolina (2022)
The present research consists of the branding development for a socks label called ‘Söco’, taking as the main element the corporate design manual. The brand aspires to combine style and creativity, with quality and comfort. Likewise, to create balance between fantasy and youth with elegance and minimalism. The aim is to reinvent this garment’s supply in the local fashion industry through classic designs but adding a fun twist with the implementation of the graphic line and the storytelling. Also, giving relevance to an accessory that even though is not always considered relevant, it can turn out to be a great addition for teenagers and young adult’s wardrobes. Additionally, as a part of the background, the character that started the project will be introduced. Lastly, the development of the brand’s personality is complemented through digital marketing.